The sense of body-ownership gates cross-modal improvement of tactile extinction in brain-damaged patients. (June 2020) - Fossataro, C.; Bruno, V.; Bosso, E.; Chiotti, V.; Gindri, P.; Farnè, A.; Garbarini, F.
Abstract: When body ownership is impaired after brain-damage, the capacity to discriminate between one's own and others' body-parts is lost. Delusional body-ownership has been recently described in patients who misidentify someone else's limb as their own (pathological embodiment) whenever it is positioned in a body congruent position. This delusion can be frequently associated with somatosensory and attentional deficits. Here, we leveraged the phenomenon of tactile extinction, as this clinical sign can be substantially ameliorated when contralesional touches are combined with proximal visual stimulation. Is body ownership a necessary prerequisite to modulate cross-modal processing and thus reducing tactile extinction? Fourteen patients with tactile extinction (TE+) took part in the study: eight of them with pathological embodiment (E+, experimental group) and six of them without pathological embodiment (E-, control group). In two different paradigms, differing for the nature of visuo-tactile stimuli, bilateral tactile stimulation of the patients' hands was combined with visual stimuli occurring on A) their own contralesional (affected) hand, B) the examiner's hand (embodied in E+), or C) a neutral object. In both groups, visual stimuli proximal to the own hand significantly improved contralesional tactile detection, while visual stimuli occurring on the neutral object did not. Crucially, only in E+TE+ patients did visual stimuli on the examiner's (embodied) hand improve contralesional tactile detection. This finding shows that cross-modal visuo-tactile integration is conditional to body-ownership, so that it ameliorates tactile extinction when visual stimuli occur on what is believed to be one's own body. From a clinical point of view, this study suggests that the effectiveness of cross-modal rehabilitative intervention can benefit from a careful evaluation of the patients' sense of body-ownership, so often impaired after brain-damage.